Complex diversity in a mainly tropical group of ant parasitoids: Revision of the Orasema stramineipes species group (Hymenoptera: Chalcidoidea: Eucharitidae) - Burks, Roger A.; Heraty, John M.; Dominguez, Chrysalyn; Mottern, Jason L. (Zootaxa, 2018)
Twenty-nine species are recognized in the Orasema stramineipes species group, including 22 new species in what is now the most diverse species group of the New World ant-parasitoid genus Orasema Cameron. Orasema aenea Gahan syn. n. is synonymized with O. freychei (Gemignani), the holotype of which has been rediscovered. Orasema smithi Howard syn. n. is synonymized with Orasema minutissima Howard. Orasema violacea Gemignani syn. n. and its replacement name Orasema gemignanii De Santis syn. n. are synonymized with O. worcesteri (Girault). Twenty-two species are described as new: O. arimbome Dominguez, Heraty & Burks n. sp., O. carchi Heraty, Burks & Dominguez n. sp., and the following 20 species by Burks, Heraty & Dominguez: O. chunpi n. sp., O. cozamalotl n. sp., O. evansi n. sp., O. hyarimai n. sp., O. kaspi n. sp., O. kulli n. sp., O. llanthu n. sp., O. llika n. sp., O. mati n. sp., O. nyamo n. sp., O. pirca n. sp., O. pisi n. sp., O. qillu n. sp., O. qincha n. sp., O. rikra n. sp., O. taku n. sp., O. tapi n. sp., O. torrensi n. sp., O. woolleyi n. sp., and O. yaax n. sp. The stramineipes-group has much greater diversity in tropical America than outside the tropics, and is much more diverse than its sister-group, the susanae-group, which is mainly present in temperate regions of Argentina. A hypothesis of phylogenetic relationships is proposed based on an analysis of 28S-D2 rDNA and cytochrome oxidase I (COI) for 14 stramineipes-group species. Species concepts were established using both morphological and molecular data. Most species in the stramineipes-group have a tropical distribution, with only a few species in temperate regions. Ant hosts for the group include Pheidole Westwood, Wasmannia Forel, and possibly Solenopsis Westwood (Formicidae: Myrmicinae). Orasema minutissima is a common parasitoid of Wasmannia auropunctata Roger in the Caribbean and has the potential to be a biological control agent in other areas of the world. Two distinct size morphs are recognized for O. minutissima, which are correlated with attacking either Wasmannia (small morph) or different castes of Pheidole (medium to large size morphs). Some species of Orasema have been regarded as pests due to scarring or secondary infections of leaves or fruit of banana, yerba mate or blueberry, but outbreaks are rare and the threat is usually temporary.